2022
DOI: 10.1371/journal.pone.0270003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug-resistant tuberculosis: A worldwide systematic review and meta-analysis

Abstract: Background Since multidrug-resistant tuberculosis (MDR-TB) is a significant public health problem worldwide, identifying associated risk factors is critical for developing appropriate control strategies. Methods A systematic review and meta-analysis was conducted for identifying factors independently predicting MDR-TB. The random-effects model was used to determine pooled odds ratios (ORs) and respective 95% confidence intervals (CIs) for the related factors. Results Of the 2301 retrieved reports, 28 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 51 publications
0
37
0
4
Order By: Relevance
“…A recent worldwide systematic review and meta-analysis evaluated data from 28 studies and evaluated 3152 patients infected with M. tuberculosis resistant to both INH and RIH and a control group of 52,715 with drug-sensitive tuberculosis. 38 Among the 22 factors analyzed, only 4 were significantly associated with MDR-TB, previous history of tuberculosis (odds ratio 6.1), previous antituberculous therapy (odds ratio 5.4), sputum positive for acid-fast bacilli (odds ratio 1.7), and lung cavity visible on radiograph (odds ratio 1.5). Factors not associated with MDR-TB included age, history of incarceration, alcohol abuse, smoking, and comorbid conditions (chronic obstructive lung disease, HIV infection, and diabetes mellitus).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent worldwide systematic review and meta-analysis evaluated data from 28 studies and evaluated 3152 patients infected with M. tuberculosis resistant to both INH and RIH and a control group of 52,715 with drug-sensitive tuberculosis. 38 Among the 22 factors analyzed, only 4 were significantly associated with MDR-TB, previous history of tuberculosis (odds ratio 6.1), previous antituberculous therapy (odds ratio 5.4), sputum positive for acid-fast bacilli (odds ratio 1.7), and lung cavity visible on radiograph (odds ratio 1.5). Factors not associated with MDR-TB included age, history of incarceration, alcohol abuse, smoking, and comorbid conditions (chronic obstructive lung disease, HIV infection, and diabetes mellitus).…”
Section: Discussionmentioning
confidence: 96%
“…The high bacterial load suggested by the positive sputum smears discovered in a patient with a lung cavity should raise a red flag indicating that oral or intravenous drug therapy may not achieve bactericidal concentrations in the affected lesions and should lead to invasive procedures for drug administration. 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A worldwide systematic review and meta-analyses reported that AFB smear positivity, lung cavity, a history of TB disease and a history of anti-TB treatment were the risk factors associated with MDR-TB [ 39 ]. However, the multivariate analysis revealed that other parameters, such as sex, age, residential area, education, marital status, occupation, diabetes mellitus, and HIV infection could not be used as independent predictors for MDR-TB [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MTB, drug resistance develops through spontaneous genetic mutations. The development of acquired drug resistance usually occurs when there is a large bacterial population, such as in pulmonary cavities (2) or when an inadequate drug combination or dosages of the first-line drugs (FLDs) has been prescribed (3,4). Rarely, malabsorption of anti-TB drugs may account for acquired resistance (5).…”
Section: Introductionmentioning
confidence: 99%